Determination of the Energy Band Gap of Silicon Using Quantum Simulation for Photovoltaic Applications - Bilya, M. A.; Sarki, M. U.; Mundi, A. A. (Advanced Aspects of Engineering Research Vol. 2, 2021)
This research deals with the study of the band structure, and density of state of silicon, using the first-principles pseudopotential method, based on the density functional theory (DFT) and the plane-wave method as implemented into Quantum Espresso (this is an open source software for Research of the Electronic Structure, Simulations, and Optimizations of materials) package. The value of the band gap found ranges between -0.2 to +0.6 eV. From the DOS graph we can observe the peaks from – 3.0 eV to – 3.5eV, and 5.50eV to 7.5eV for Si Material.